Implementation of Hybryd Contracts in MULIA Financing Transactions at Sharia Pawnshop - Muhsin, Syamsiah; Masse, Rahman Ambo (IAIN Parepare, 2020)
This study discusses the implementation of hybrid contract in MULIA financing transactions at Sharia Pawnshop service unit, Pangkajene branch. The contract uses murabahah and Rahn contract. In this study also examined the prospects of the MULIA product marketing efforts and the challenges faced in increasing the number of customer transactions. The type of research used in this thesis is the kind of descriptive research-qualitative, is the plan and structure of the inquiry for answers to questions of researchers in the form of descriptive data are obtained from the results of the in-depth interviews with the informant, observations and collect and analyze data in the form of the document and then do some checking of data with the technique of triangulation. The result of this study found some results that Sharia Pawnshop service unit, Pangkajene branch has implemented with either some provision in the MULIA transaction in accordance with the fatwa but some other of fatwa not implemented yet, for example in terms of the object of the contract should be the property of the Sharia Pawnshop before selling it to the customer also about provisions dealing with procedures using two contracts in one transaction.